1962
DOI: 10.1139/m62-064
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of the Blood of Actively Immunized Wax Moth Larvae

Abstract: The blood of normal wax moth larvae is not bactericidal for Pseudonzo?tas aerzrginosa. The blood becomes moderately bactericidal when larvae are actively immunized against P. aerzrginosa. This activity was measured b y a modification of Nagington's technique for the estimation of typhoid antibody. Bactericidal activity appears t o be the only measurable type of antibody response against P. aerrrginosa. Cell-free blood was as active as whole blood; 0.02 ml of immune serum kills about 1000 organisms. The blood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…1). Reduced susceptibility to Photorhabdus appeared rapidly, within a few hours, and persisted for at least 48 h. This is consistent with previous observations (Stephens, 1959(Stephens, , 1962 in which immunity was induced within hours of exposure to microbial pattern molecules. There was no sign in our experiments of any decline in immunity during the 48 h period of the experiment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…1). Reduced susceptibility to Photorhabdus appeared rapidly, within a few hours, and persisted for at least 48 h. This is consistent with previous observations (Stephens, 1959(Stephens, , 1962 in which immunity was induced within hours of exposure to microbial pattern molecules. There was no sign in our experiments of any decline in immunity during the 48 h period of the experiment.…”
Section: Discussionsupporting
confidence: 92%
“…We considered it inappropriate to extend the duration of the experiment beyond this time, because at later times the control insects would be preparing to pupate, when new immune defences begin to appear according to a developmental programme (Dunn et al, 1994). In previous work with Galleria mellonella larvae (Stephens, 1959(Stephens, , 1962 immunity induced by injection of killed P. aeruginosa cells was found to decline after about 24 h. The possibility that the progressive loss of immunity with time seen in Stephens' experiment was due to the onset of pupation cannot be excluded. Further work is required to define more precisely the duration of the protection afforded by pre-infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Stephens (46,47) had reported that immunization was accompanied by a loss of the ability of the hemolymph to melanize I decided to see if rnelanization times could be used as an index of immunity. This should be possible if the inverse relationship described by Stephens (46,47) and by Taylor (49) is a result of immunization.…”
Section: Can Detoxified Cell Wall Immunize?mentioning
confidence: 99%